Terpaan Media Massa dan Turbulensi Budaya Lokal - Tulasi, Dominikus (Humaniora, 2012)
The attack of mass media in digital era now is an inevitability of the advanced information communication technology. The development of media relation in the current time also shows a higher scientific human existence. And, the side effect of those advances is the ultimate culture turbulence across developing countries. The sophisticated information communication technology at the present time has been victimizing young generation particularly in under developed countries. The power of media is a matter of fact which showing the domination influence of advance nations. In the other hand, the local culture of the victimized countries though still exists, but ultimately is the overwhelmed market of the media goal itself. The hegemony of media influence is the objective of advanced countries to dominate all aspect of weak countries including Indonesia. The global dominanace of advance country like American media is often resented overseas.